2020
DOI: 10.3390/molecules25122883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pyrrole-Imidazole Polyamides Targeting Human TGF-β1 on the Malignant Phenotypes of Liver Cancer Cells

Abstract: Synthetic pyrrole-imidazole (PI) polyamides bind to the minor groove of double-helical DNA with high affinity and specificity, and inhibit the transcription of corresponding genes. In liver cancer, transforming growth factor (TGF)-β expression is correlated with tumor grade, and high-grade liver cancer tissues express epithelial-mesenchymal transition markers. TGF-β1 was reported to be involved in cancer development by transforming precancer cells to cancer stem cells (CSCs). This study aimed to evaluate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In particular, an immunohistochemical study revealed a complete inhibition of TGF-β1 staining in the medulla of the kidneys of marmosets. In subsequent studies, the inhibitory effect of PI polyamide on the synthesis of TGF-β1 in diabetic nephropathy 18 and in liver and lung cancer cells 19 was confirmed. Thus, the researchers proved the selectivity and efficiency of the structure they designed.…”
Section: Discussionmentioning
confidence: 83%
“…In particular, an immunohistochemical study revealed a complete inhibition of TGF-β1 staining in the medulla of the kidneys of marmosets. In subsequent studies, the inhibitory effect of PI polyamide on the synthesis of TGF-β1 in diabetic nephropathy 18 and in liver and lung cancer cells 19 was confirmed. Thus, the researchers proved the selectivity and efficiency of the structure they designed.…”
Section: Discussionmentioning
confidence: 83%
“…46 TGF-β is involved in tumorigenesis. 47 Thus, the similarity may due to various functions of TGF-β.…”
Section: Discussionmentioning
confidence: 99%
“…Takagi et al. (2020) 89 also examined the effects of the PIP targeting human TGF‐β1 on the malignant phenotypes of liver cancer cells, which showed suppression in the migration and invasion of liver cancer cells and reduction in TGF‐β1‐induced epithelial‐mesenchymal transition, and in vivo tumor growth inhibition. Otsuki et al.…”
Section: Designing Pips To Modulate Diverse Transcriptional Targetsmentioning
confidence: 99%